Enhancement of CRISPR/Cas12a trans-cleavage activity using hairpin DNA reporters. Issue 14 (13th July 2022) - Rossetti, Marianna; Merlo, Rosa; Bagheri, Neda; Moscone, Danila; Valenti, Anna; Saha, Aakash; Arantes, Pablo R; Ippodrino, Rudy; Ricci, Francesco; Treglia, Ida; Delibato, Elisabetta; van der Oost, John; et al.
Abstract: The RNA programmed non-specific ( trans ) nuclease activity of CRISPR-Cas Type V and VI systems has opened a new era in the field of nucleic acid-based detection. Here, we report on the enhancement of trans -cleavage activity of Cas12a enzymes using hairpin DNA sequences as FRET-based reporters. We discover faster rate of trans -cleavage activity of Cas12a due to its improved affinity ( K m ) for hairpin DNA structures, and provide mechanistic insights of our findings through Molecular Dynamics simulations. Using hairpin DNA probes we significantly enhance FRET-based signal transduction compared to the widely used linear single stranded DNA reporters. Our signal transduction enables faster detection of clinically relevant double stranded DNA targets with improved sensitivity and specificity either in the presence or in the absence of an upstream pre-amplification step. Graphical Abstract: